Comprehensive evaluation of gradient controlled anaerobic digestion and pyrolysis integration processes: A case study of Sargassum treatment. (February 2022) - Wang, Zhi; Li, Jian; Yu, Fan; Yan, Beibei; Chen, Gaunyi
Graphical abstract: Highlights: An integrated process of anaerobic digestion (AD) and pyrolysis (PY) was proposed. PY performance of sargassum (SA) was enhanced by gradient controlled AD. PY gases evolution changed due to the destruction of SA structure by AD. The maximum energy recovery of the integration (AD for 14 days) was 6.42 MJ/kg TS. Abstract: In this study, an integrated process of gradient controlled anaerobic digestion (AD) and pyrolysis (PY) was proposed for energy recovery of Sargassum (SA). The methanogenic performance of SA and the PY performance of subsequent digestate were investigated. And the energy flow of the integrated process was comprehensively evaluated. The results showed that two methanogenic peaks occurred, which were appeared on the 7th day (9.57 mL/g VS) and the 17th day (15.74 mL/g VS), respectively. The structure and toughness of SA were destroyed by AD, which altered the subsequent PY performance. For the energy flow, the AD (lasted for 14 days) integrated PY process showed a superior performance compared with direct PY, as the total energy recovery increased from 5.88 to 6.42 MJ/kg TS. This study laid a foundation for the successful integration of AD and PY, which provided a guidance for the clean treatment and energy recovery of biomass.